Culturally and linguistically appropriate home visit intervention for underserved dementia family caregivers: Preliminary results from a randomized controlled trial. (20th December 2022) - Lee, Jung‐Ah; Ju, Eunae; Zhang, Jiuchen; Sabino‐Laughlin, Eilleen; Rahmani, Amir; Gibbs, Lisa; Shin, Sanghyuk; Qu, Annie; Kehoe, Priscilla; Nyamathi, Adey
Abstract: Background: Family caregivers of persons with dementia (PWD) suffer from stress and negative health outcomes related to round‐the‐clock caregiving responsibilities. Often caregivers lack awareness of community resources. Community Health Workers (CHW) have proven effective in educating families and can implement interventions that aim to reduce the impact of stress on their health. To alleviate caregiver burden among dementia family caregivers, this study has CHWs' visit family caregivers' homes offering education, stress reduction, and compassionate support/listening. Methods: Participants were recruited from Southern California via non‐profit organizations, senior centers, and adult day services. Participants were randomly assigned to CHW home‐visit intervention group (IG) or control group (CG) with resource information only. The intervention includes stress reduction techniques of mindful breathing and compassionate support/listening, (2) education on dementia caregiving skills to handle difficult behaviors of PWD, and (3) resource information. The 3‐month intervention is given by bilingual CHWs who speak English, Spanish, Vietnamese, or Korean. A linear mixed model was used to compare differences from baseline to 3‐month on each outcome (caregiver burden, PWD behaviors ‐ memory, distress, disruption) between IG and CG. Exit interviews were conducted for IG participants. Results: 26 family caregivers participated in the study (12 Korean, 9 Vietnamese, 3 Hispanic, 2 Caucasian); 14 spouses (54%), 12 off‐spring (46%); 18 females (69%), age from 34 to 89 (mean = 66.8 sd = 12.6). IG Participants showed a significant decrease in caregiving burden compared to CG (coefficient = ‐7.68, p = .0041). PWD behaviors were significantly decreased from baseline to 3 months but no difference by group. However, there was a trend for improvement of PWD's memory problems in the IG compared to the CG (coefficient = ‐2.43, p = .056). Language specific exit interviews showed that educational materials were valuable and communication skills training was helpful as was CHW home visits. Most participants reported the benefit of mindful breathing and practiced it when overwhelmed or having sleep problems. The overall satisfaction of the intervention was high (mean = 4.4 of 5). Recruitment is on‐going but challenging during the pandemic. Conclusion: Preliminary results showed the CHW led home‐visit intervention helped improve burden and PWD memory problems and was acceptable by the family caregivers of PWD.